USE OF ANTIPSYCHOTICS AND BODY MASS INDEX OF SCHIZOPHRENIC PATIENTS IN INDONESIA - Hayatul Maulida; Cut Husna; Marthoenis Marthoenis (RADJA PUBLIKA, 2023)
The use of antipsychotics in schizophrenic patients has side effects during their use; changes that occur in people with mental disorders while taking drugs will certainly be related to the part and structure of the body's metabolism that is affected by the drug, causing changes in body weight of schizophrenic patients. This study aimed to identify the relationship between antipsychotic use and body mass index in schizophrenic patients. This cross-sectional study was conducted among patients with schizophrenia under antipsychotic medication. The research instruments used in the study are sociodemographic instruments and types of drug use. It was found that most of the patients were overweight (39%) and obese (38%), the majority of patients took second-class antipsychotic drugs (81%), and only some of them received first-class antipsychotics (19%). The increased use of second-generation antipsychotics and increased rate of overweight and obesity among patients with schizophrenia should receive special attention.